2009
DOI: 10.1063/1.3176507
|View full text |Cite
|
Sign up to set email alerts
|

The resolution of the identity approximation applied to the correlation consistent composite approach

Abstract: A new implementation of the correlation consistent composite approach (ccCA), denoted RI-ccCA, utilizing both the resolution of the identity (RI) and local methods is presented. A set of 102 molecules composed of first and second row, main group atoms is employed to compare total energies, atomization energies, and enthalpies of formation between the original ccCA implementation and those of RI-ccCA. Relative CPU time and disk space requirements of RI-ccCA as compared to ccCA, demonstrate that on the average, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…the G3/05 test set of 454 experimental energy differences) to deal with deficiencies in many of the approximations to Eqn (1.2) leading to the inclusion of an empirically based higher level correction. Their correlation-consistent composite approach (ccCA) has been applied to a range of elements including first-row transition metals [33,34,35,36,37,38]. Both the Gn and Petersson CBS methods can be readily accessed in the Gaussian programs by a single keyword as can the W1 method noted next.…”
Section: Computational Approach To Reliable Thermochemical Predictionsmentioning
confidence: 99%
“…the G3/05 test set of 454 experimental energy differences) to deal with deficiencies in many of the approximations to Eqn (1.2) leading to the inclusion of an empirically based higher level correction. Their correlation-consistent composite approach (ccCA) has been applied to a range of elements including first-row transition metals [33,34,35,36,37,38]. Both the Gn and Petersson CBS methods can be readily accessed in the Gaussian programs by a single keyword as can the W1 method noted next.…”
Section: Computational Approach To Reliable Thermochemical Predictionsmentioning
confidence: 99%
“…[15] Some commonly used composite methodologies include the Gaussian-n (Gn) methods, [15][16][17][18][19] Weizmann-n (Wn) methods, [20][21][22] the Feller-Peterson-Dixon (FPD) procedure, [3,23,24] HEAT method, [25] the multi-coefficient methods of Truhlar and coworkers, [26] and the correlation consistent Composite Approach (ccCA), developed by Wilson and coworkers. [27][28][29][30][31][32][33][34][35][36] ccCA includes extrapolation of energies to the CBS limit and the addition of core-valence electron interactions within the methodology to account for important effects that may not be computationally feasible to recover in a single point calculation.…”
Section: Introductionmentioning
confidence: 99%
“…[19] These molecule sets have been used as a gauge for variants of ccCA in earlier work. [27][28][29][30][31][32][33][34][35][36]41] ccCA is routinely able to achieve a mean absolute deviation (MAD) of less than 1 kcal mol -1 , on average, in the calculation of energetic properties (i.e., ΔH f 's, ionization potentials, and electron affinities) for the molecules in these sets. Further, ccCA has been utilized to study nearly two thousand molecules, covering a large portion of the periodic table, and properties including pK a 's, [36] reaction barriers, [42] and potential energy curves for ground and excited state species, [31,[43][44][45] in addition to the energetic properties mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Additional computations are then utilized to approximate higher‐order correlation effects and account for scalar relativistic effects. In previous studies, ccCA has been shown to predict enthalpies of formation, ionization potentials, electron affinities, activation energies, isomerization energies, and BDEs to within 1 kcal mol −1 (on average) of well‐established experiment for main group species[36–38, 44–46] and to within 3 kcal mol −1 (known as transition metal chemical accuracy), on average, for transition metal species. [47, 48]…”
Section: Introductionmentioning
confidence: 99%